THE EFFECTS OF EXERCISE ON ACADEMIC AND COGNITIVE PERFORMANCE IN ATHLETES - Kumar, Raj; Singh, Gurdeep (International Journal of Psychosocial Rehabilitation, 2021)
Younger generations worldwide are increasingly sedentary compared to previous generations. Physical exercise has a positive impact on human growth and development, providing both physiological and psychological benefits. In this research, 80 Italian elementary (primary) school students, aged approximately 11.0 ± 0.3 years, with an average height of 1.46 ± 0.09 meters and a weight of 39.5 ± 7.9 kilograms, were surveyed. The study aimed to explore connections between physical test results and academic performance, examining reciprocal links among socio-demographic factors, family environment, lifestyle (including physical activity), and school performance using a structural modeling technique. Each child’s lower and upper limb muscular strength, running speed, and agility were assessed. Pearson’s correlation was used to analyze the relationship between physical test scores and academic achievement. Results showed that agility was positively correlated with higher scores in languages (Italian, German, and English), as well as in the arts, including music and physical education. Marks in mathematics, physical education, and technology were associated with sprint performance. Aside from the connections between physical education marks and physical tests, all correlation coefficients were modest, indicating a moderate to strong correlation. The structural model revealed that socio-demographics and lifestyle had a significant impact on school performance. Notably, lifestyle was found to completely mediate the influence of the home environment on educational success. Providing opportunities for physical activity at school and at home is crucial for improving children’s health and well-being.